The Locality and the Immediate Realities: Tracing Modernity in Indonesian and Malaysian Modern Art - Abdullah, Sarena; Thiruchelvam, Chelliah (Leutikaprio, 2015)
The modem as defined by Baudelaire refers to the current or contemporary developments. Modern art starts with artworks that represent the vignettes of daily life in the privacy of private studios in Paris to the beauty of modern life seen from multiple surroundings. The appropriation and mutation of modernity by Africans, Arabs, lndians, and Asians, for example, do not indicate Westernization but rather an actjve participation in the construction of modemism by non-European sources. Jim Supangkat terms it as "multi-rnodernism" in which he argues for nonEuropean modernism to be contextualizcd, articulated, and theorized within their own specific historicity (Supangkat, 1997). Within this context, this paper attempts to discuss the context of early modernity of modern art specifically in Indonesia and Malaysia. ms paper will argue that modernity does not only belong to the West but it can be multiplied and pluralized over its Western origin. Therefore, this paper upholds that modern art that was accepted and developed in the non-Wcstem world is a form of a discursive formation, which continues to be 'underconstruction' that is multifaceted and yet an intricate subject of study, in which this paper attempts to unfold.